Study of the adsorption of reactive blue 50 on zero valent iron - Sarangerel, D; Altangerel, A; Munkhzaya, B; Sukhbaatar, B (Mongolian Journal of Chemistry, 2014)
In this study, removal efficiency of the Reactive blue 50 and adsorption mechanism on the zero valent iron were investigated. Reactive blue 50 which is used to wool and cashmere dyeing were selected due its non-biodegradable and metabolic stability. Zero valent iron particle has been synthesized by chemical method. A systematic characterization of zero valent iron was performed using X-ray diffractometer, scanning electron microscope and infrared spectrometer analysis. The optimal condition of adsorption was determined as initial reactive dye 50 concentration of 150 mg·L-1, zero valent iron mass of 0.2 g and solution pH of 6.0 at room temperature. At optimal condition, organic dye removal in a real wastewater sample from Tsombon Knit LLC was 99.5%. Mongolian Journal of Chemistry 15 (41), 2014, p21-26